Ceftriaxone Treatment Preserves Cortical Inhibitory Interneuron Function via Transient Salvage of GLT-1 in a Rat Traumatic Brain Injury Model. (22nd December 2018) - Hameed, Mustafa Q; Hsieh, Tsung-Hsun; Morales-Quezada, Leon; Lee, Henry H C; Damar, Ugur; MacMullin, Paul C; Hensch, Takao K; Rotenberg, Alexander
Abstract: Traumatic brain injury (TBI) results in a decrease in glutamate transporter-1 (GLT-1) expression, the major mechanism for glutamate removal from synapses. Coupled with an increase in glutamate release from dead and dying neurons, this causes an increase in extracellular glutamate. The ensuing glutamate excitotoxicity disproportionately damages vulnerable GABAergic parvalbumin-positive inhibitory interneurons, resulting in a progressively worsening cortical excitatory:inhibitory imbalance due to a loss of GABAergic inhibitory tone, as evidenced by chronic post-traumatic symptoms such as epilepsy, and supported by neuropathologic findings. This loss of intracortical inhibition can be measured and followed noninvasively using long-interval paired-pulse transcranial magnetic stimulation with mechanomyography (LI-ppTMS-MMG). Ceftriaxone, a β-lactam antibiotic, is a potent stimulator of the expression of rodent GLT-1 and would presumably decrease excitotoxic damage to GABAergic interneurons. It may thus be a viable antiepileptogenic intervention. Using a rat fluid percussion injury TBI model, we utilized LI-ppTMS-MMG, quantitative PCR, and immunohistochemistry to test whether ceftriaxone treatment preserves intracortical inhibition and cortical parvalbumin-positive inhibitory interneuron function after TBI in rat motor cortex. We show that neocortical GLT-1 gene and protein expression are significantly reduced 1 week after TBI, and this transient loss is mitigated by ceftriaxone. Importantly, whereas intracortical inhibition declines progressively after TBI, 1 week of post-TBI ceftriaxone treatment attenuates the loss of inhibition compared to saline-treated controls. This finding is accompanied by significantly higher parvalbumin gene and protein expression in ceftriaxone-treated injured rats. Our results highlight prospects for ceftriaxone as an intervention after TBI to prevent cortical inhibitory interneuron dysfunction, partly by preserving GLT-1 expression.